2009
DOI: 10.4269/ajtmh.2009.81.34
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Visceral Leishmaniasis in a New Epidemic Site in Amhara Region, Ethiopia

Abstract: We conducted a case-control study to evaluate risk factors for visceral leishmaniasis during an epidemic in a previously unaffected district of Ethiopia. We also collected blood and bone marrow specimens from dogs in the outbreak villages. In multivariable analyses of 171 matched case-control pairs, dog ownership, sleeping under an acacia tree during the day, and habitually sleeping outside at night were associated with significantly increased risk. Specimens from 7 (3.8%) dogs were positive by immunofluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
81
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 29 publications
15
81
1
1
Order By: Relevance
“…The minimum age was 5 years and maximum age was 70 years, which was consistent with results of other studies in Brazil, but were less than those of India (mean age, 45 years) [6,14,15]. Sixty-one patients (44.2%) were males, and the mean age was 29.65±11.10 years, which come in line with others [15]. The rest of the patients were females with a mean age of 26.12±11.89 years, minimum age of 5 years, and maximum age of 70 years, which was contrary to results of an Indian study indicated that 93% of affected patients were males.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The minimum age was 5 years and maximum age was 70 years, which was consistent with results of other studies in Brazil, but were less than those of India (mean age, 45 years) [6,14,15]. Sixty-one patients (44.2%) were males, and the mean age was 29.65±11.10 years, which come in line with others [15]. The rest of the patients were females with a mean age of 26.12±11.89 years, minimum age of 5 years, and maximum age of 70 years, which was contrary to results of an Indian study indicated that 93% of affected patients were males.…”
Section: Discussionsupporting
confidence: 82%
“…The rest of the patients were females with a mean age of 26.12±11.89 years, minimum age of 5 years, and maximum age of 70 years, which was contrary to results of an Indian study indicated that 93% of affected patients were males. In Brazil, 65% of Kala -azar patients were males and in Ethiopia they represents (74%-85.6%) [6,[14][15][16]. High male patient load could be because of the economic activities that entail sex bias.…”
Section: Discussionmentioning
confidence: 99%
“…Age wise distribution of human leishmaniasis in the study site indicated that it is more common in populations with age of 15 years and above with the rate of 94% similar to [9] who indicated that these adult human beings older than 15 years were more affected compared to the lower age groups. At the same time, [15] indicated that 3.3% children younger than 5 years, 19.2% of children 5-14 years, and 8.6% of adults 40 years or older were affected.…”
Section: Discussionmentioning
confidence: 97%
“…Since the epidemic of disease is chracterized by high mortality in adults, high disease incidence was observed in age 15-45 groups. The Northwestern VL focus in Ethiopia covers the Semiarid Metemma and Humera plains in Tigray and Amhara regional states bordering Sudan [9].…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, specificity evaluation was conducted using specimens from healthy controls from the same disease-endemic area. 20 Cases were defined based on the Médecins Sans Frontières VL case definition as modified for a malaria-endemic area, requiring fever for > 2 weeks, splenomegaly and/or abdominal swelling, and/or weight loss; malaria was ruled out based on a rapid antigen detection test. 21 Patients who fulfilled this case definition were eligible to participate as suspected VL patients.…”
Section: Introductionmentioning
confidence: 99%